Statistical Analysis of the Performance of a Big and Open Economy: The Case of the U.S. - Zhuravliov, O. V.; SimachovaО. М. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The US economy is one of the richest and most diversified economies in the world and keeps its leadership in the global economy for the past 100 years. The United States is a global leader in computer technology, pharmaceuticals and the manufacture of medical, aerospace and military equipment. And although services make up about 80% of GDP, the US remains the second largest producer of industrial goods in the world and is a leader in research and development. President Donald Trump was elected in November 2016, promising a big gap with his predecessor’s regulatory, tax and trade policies. Therefore, the current socio-economic status of the USA and the possible ways of its development in the future are interesting for studying the impact on other economies, in particular, on the Ukrainian economy and the search for new and optimal ways of developing relations between the United States and Ukraine. Key macroeconomic indicators of the US economy in 2011–2018 are analyzed, demonstrating the influence of Donald Tramp’s new policy on changes in the indicators of the economy, the labor market, trade, etc., as well as possible ways of development in the coming years. The review of key macroeconomic indicators gives grounds for classifying the American economy as healthy one. Rates of GDP growth will remain in the range of 2 to 3%. These rates of growth in the world’s largest economy are callable to ensure a substantial increase in the global activity. But uncertainties in the politics may hinder global growth and have clearly negative impact on the investment growth in developed and developing economies.